ECONOMIC RESULTS OF INDUSTRIAL ESTABLISHMENTS ACTIVITY IN KAZAN FOR 1895-1896. (EXPERIENCE OF THE STATISTICAL ANALYSIS) - D. A. Sergeev; I. I. Mingaleev (Russian Journal of Economics and Law)
The article is devoted to the statistical analysis of economic activity results of industrial establishments in Kazan for 1895-96. The interrelation of economic, technological and organizational processes allowing evidently to open specificity of an intensification mechanisms of production on industrial establishments in Kazan for the considered period is tracked.